A study to assess the effectiveness of breast feeding technique in prevention of nipple soreness among primipara mothers, Chennai . - S.TAMILSELVI, (International Journal of Pharma and Bio Sciences, 2017)
Breast-feeding is good for new mothers as well as for their babies. There are no bottles to sterilize and no formula to buy, measure and mix. It may be easier for a nursing mother to lose the pounds of pregnancy as well, since nursing uses up extra calories. Lactation also stimulates the uterus to contract back to its original. the effectiveness of teaching programme regarding breastfeeding techniques on knowledge and practice in preventing nipple sore. Experimental Group –Primipara postnatal mothers who can give breast feeding and who do not have nipple soreness are selected. Breast feeding techniques taught 10 minutes before starting breast feeding, followed with 10 minutes demonstration and 10 minutes video. Control Group –Primipara postnatal mothers who are not provided interventions. This is an experimental study. the samples were selected by simple random sampling technique ,two group pre test post design was adopted the data was collected and analysed by SPSS statistical package .In this study, effectiveness of breast feeding technique assessed in prevention of nipple soreness .The study is conducted at the postnatal ward. Ayanavaram. The results revealed that breast feeding technique had a significant effect in preventing nipple soreness. Majority of the primipara postnatal mothers in the experimental group were prevented from nipple soreness than the patients in the control group who experienced breast feeding induced nipple soreness.